2019
DOI: 10.1016/j.chest.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Respiratory Microbiota Profiles Are Associated With Lower Airway Inflammation in Children With Protracted Bacterial Bronchitis

Abstract: BACKGROUND: Effective management of protracted bacterial bronchitis (PBB) is needed to prevent chronic disease (eg, bronchiectasis). Understanding the contributions of ongoing airway infection and inflammation is important to achieving optimal PBB treatments. The aim of this study was to compare BAL microbiota, bacterial biomass, and inflammatory markers in children with PBB and age-matched control patients.METHODS: BAL was prospectively collected from 28 children with PBB (median age, 1.7 years; range, 0.6-7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
2
25
0
2
Order By: Relevance
“…Co-infection could be found in the identified studies, some patients were caused by multiple bacteria and several cases were co-infected by bacteria and viruses [1,14]. Consistent with the findings, microbiota dysbiosis can be found in the BALF of patients with PBB [23] and the inflammation may not be driven by single bacteria [24]. Viruses also can be detected in BALF of patients with PBB, however, there was no evidence to prove that PBB was virus-induced [25].…”
Section: Discussionsupporting
confidence: 53%
“…Co-infection could be found in the identified studies, some patients were caused by multiple bacteria and several cases were co-infected by bacteria and viruses [1,14]. Consistent with the findings, microbiota dysbiosis can be found in the BALF of patients with PBB [23] and the inflammation may not be driven by single bacteria [24]. Viruses also can be detected in BALF of patients with PBB, however, there was no evidence to prove that PBB was virus-induced [25].…”
Section: Discussionsupporting
confidence: 53%
“…35 Prevotella species have been associated with protracted bacterial bronchitis in children. 36 In a study of subjects with stable COPD, increased bacterial burden in the airways was associated with FEV 1 decline over time. The common bacteria that were cultured from sputum included Streptococcus viridans, Nesseria spp., Corynebacterium, as well as Hemophilus spp., all of which are normal oral flora.…”
Section: Aspiration Of Oral Bacteriamentioning
confidence: 99%
“…Moreover, children with PBB showed that a higher BAL bacterial biomass strongly correlated with neutrophilic inflammation. PBB-microbiota were different to control-microbiota and clustered into four distinct microbiota patterns where respiratory pathogen or other microbiota species (e.g., Prevotella ) have been detected ( 25 ). The cultures of respiratory pathogens, inflammatory markers, and BAL bacterial biomass were found to not be associated with this variation in alpha diversity among subjects with PBB.…”
Section: Etiopathogenesismentioning
confidence: 99%